Pengaruh Environmental Awareness Terhadap Green Purchase Intentions yang Dimediasi oleh Green BeautyProduct Knowledge dan Environmental Concerns pada Green Beauty Product Garnier - Tafiana, Adinda Kalitta; Tantra, Tarandhika (Jurnal Ilmu Manajemen, 2023)
According to BPOM, the cosmetics industry has increased by 20.6% up to July 2022. According to the Cosmetic Packaging Market Growth, Trends, and Forecast 2020, almost 50% of cosmetic packaging is made of plastic. This is supported by the increase in online shopping activities during the pandemic, which has increased by 25%-30%, meaning that the waste from used products has also increased, and the sector that dominates the most is the cosmetics sector. Not all cosmetics, such as skincare or face and body treatments, have a negative impact. Since 2020, Garnier has transformed into one of the green beauty products.This research uses a quantitative method by examining cause and effect and focusing on research variables. The study aims to see if there is a direct effect of Environmental Awareness on Green Product Knowledge and Environmental Concerns, direct and indirect effects on Green Purchase Intentions for Garnier by Green Product Knowledge and Environmental Concerns. Data analysis is carried out using Covariant-Based Structural Equation Model (CB-SEM) with AMOS 26 software.The study shows a significant and positive direct influence of Environmental Awareness on Green Product Knowledge and Environmental Concerns, Environmental Concerns on Green Purchase Intentions, and Environmental Concerns playing a positive mediating role. However, Green Product Knowledge shows no significant influence on Green Purchase Intentions, also in mediating between Environmental Awareness and Green Purchase Intentions.